2012
DOI: 10.1007/s00011-012-0572-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced apoptosis correlates with enhanced autophagy in synovial tissues of rheumatoid arthritis

Abstract: The impaired apoptosis in RA synovium might result from increased autophagy, which in turn could be due to the deregulation of miRNA-30a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 31 publications
5
82
1
Order By: Relevance
“…We have observed that the CXCR3-B-mediated signal down-regulates autophagy in breast cancer cells. It has been established that there can be a reverse correlation in the regulation of apoptosis and autophagy (34), which is clearly supportive to our findings. In addition, it has been demonstrated that autophagy can delay apoptotic death in MCF-7 cells (35).…”
Section: Discussionsupporting
confidence: 92%
“…We have observed that the CXCR3-B-mediated signal down-regulates autophagy in breast cancer cells. It has been established that there can be a reverse correlation in the regulation of apoptosis and autophagy (34), which is clearly supportive to our findings. In addition, it has been demonstrated that autophagy can delay apoptotic death in MCF-7 cells (35).…”
Section: Discussionsupporting
confidence: 92%
“…Ex vivo studies show that the rate of apoptosis in RA FLS has an inverse relationship to the expression of beclin1 and LC3 (REF. 99). Furthermore, inhibition of proteasomal activity in RA FLS increases their LC3II protein levels and prolongs their survival 100 , suggesting that increased autophagy in RA FLS promotes RAassociated synovitis.…”
Section: Autophagy In Rheumatic Diseasesmentioning
confidence: 93%
“…These RA FLS show signs of myofibroblast differentiation (an intermediate cell type between a smooth muscle cell and a fibroblast), such as increased collagen deposition and expression of αsmooth muscle actin, which contribute to syno vial fibrosis 97 . In RA FLS, multiple mechanisms confer resistance to programmed cell death, including increased levels of antiapoptotic factors, downregulation of proap optotic factors 98 and increased autophagy [99][100][101][102] . Ex vivo studies show that the rate of apoptosis in RA FLS has an inverse relationship to the expression of beclin1 and LC3 (REF.…”
Section: Autophagy In Rheumatic Diseasesmentioning
confidence: 99%
“…Therefore, when RASFs were exposed to ER stress, high level of autophagy is induced and it may contribute to resistance against ER stress-induced cell death [67]. Furthermore, decreased level of miR-30a, which was shown to inhibit Beclin-1 expression, was observed in synovial tissue of RA, and it may contribute to upregulation of autophagy in RASFs [68]. Recently, dual role of autophagy has been investigated in RASFs in response to cellular stress [69].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%